Giant energy density and high efficiency achieved in bismuth ferrite-based film capacitors via domain engineering - Hao Pan (Nature Portfolio, 2018)
Dielectrics with high capacitive energy storage density are essential for modern electrical devices and pulsed power systems. Here, the authors realised superior energy storage performance in lead-free bismuth ferrite-based relaxor ferroelectric films through domain engineering.